MODERN DIAGNOSIS AND TREATMENT OF ECZEMA (International journal of artificial intelligence, 2024)
Eczema (eg-zuh-MUH) is the name for a group of inflammatory skin conditions that cause itchiness, dry skin, rashes, scaly patches, blisters and skin infections. There are seven different types of eczema: atopic dermatitis, contact dermatitis, dyshidrotic eczema, nummular eczema, seborrheic dermatitis and stasis dermatitis. For lighter skin, eczema can present as red, inflamed skin. For darker skin tones, eczema can present as brown, purple, gray or ashen. Itchy skin is the most common symptom of eczema.